Suicide by Inhalation of Suffocative Gas - Büyük, Yalçın; Aslıyüksek, Hızır; Eke, Murat; Bulut, Ragıp Erkut; Gürpınar, Süleyman Serhat (The Bulletin of Legal Medicine, 2005)
LPG is a by-product of petroleum refining and is a colourless gas with a mild odour. A foul odorant such as ethanethiol is added before commercially presented. LPG is highly flammable and has a high fire and explosive hazard. LPG is commercially available as propane, butane and propane-butane mixtures. Propane is a colourless and odourless flammable gas. Butane is a colourless and flammable gas with a gasoline-like or natural gas odour. Suicide by LPG inhalation was relatively common due to widespread availability of installation systems. Currently suicide by inhalation of these gases is rare due to changing trends, and only a few case reports about death following accidental or intentional inhalation of LPG have been reported recently. Sudden death due to inhalation of these gases in abusers is the most encountered condition. This case report is about a 65 years old man found dead in his bed holding a LPG tube near his mouth and nose. Inhalation of suffocative gas was determined to be the cause of death based on autopsy findings and the scene investigation. This paper discusses the medico-legal approach for this type of intoxication cases. Key words: LPG, butane, propane, suicide, autopsy